REDUCTION INSHIPMENT DELINQUENCIES ANDPRODUCT LEAD TIME ONENHANCING CUSTOMER SERVICE: A CASE STUDY - kumar, Gopa; k, Jayaraman; Kiumarsi, s (The International Journal of Accounting and Business Society, 2014)
Abstract: REDUCTION INSHIPMENT DELINQUENCIES ANDPRODUCT LEAD TIME ONENHANCING CUSTOMER SERVICE: A CASE STUDY. Customer service plays an important role in an organization's ability to generate income and revenue. From this perspective, customer service should be included as part of an overall approach to systematic improvement. A customer service experience can change the entire perception a customer has of the organization. The present paper identifies the current weaknesses of an electronic companyin terms of shipment delinquencies and long product lead-times and to propose recommendations to the company to overcome the issues towards enhancing customer service. The paper investigates the organizationsâ€™ internal and external environment factors towards establishing strengths and opportunities and further analyzing the various problems faced in order to establish the root-cause components. A list of recommendations are proposed through which the company may be able to enhance its level of customer service, increase its market share and sustain in the industry as a serious and viable contender. Â  Keyword: Shipment; Lead-Time; Product Inventory; Customer Service